Compensation of Wild Plants Weakens the Effects of Crop-Wild Gene Flow on Wild Rice Populations - Ouyang, Dongxin; Dong, Shanshan; Xiao, Manqiu; You, Jianling; Zhao, Yao; Wang, Yuguo; Zhang, Wenju; Yang, Ji; Song, Zhiping (Frontiers in Plant Science, 2021)
Crop-wild gene flow may alter the fitness of the recipient i.e., crop-wild hybrids, then potentially impact wild populations, especially for the gene flow carrying selective advantageous crop alleles, such as transgenes conferring insect resistance. Given the continuous crop-wild gene flow since crop domestication and the occasionally stressful environments, the extant wild populations of most crops are still “wild.” One interpretation for this phenomenon is that wild populations have the mechanism buffered for the effects of crop alleles. However, solid evidence for this has been scarce. We used wild rice (Oryza rufipogon) and transgenic (Bt/CpTI) rice (O. sativa) as a crop-wild gene flow model and established cultivated, wild, and F7 hybrid rice populations under four levels of insect (Chilo suppressalis) pressure. Then, we measured the trait performance of the plants and estimated fitness to test the compensatory response of relatively high fitness compared to the level of insect damage. The performance of all plants varied with the insect pressure level; wild plants had higher insect-tolerance that was expressed as over- or equal-compensatory responses to insect damage, whereas crop and hybrids exhibited under-compensatory responses. The higher compensation resulted in a better performance of wild rice under insect pressure where transgenes conferring insect resistance had a somewhat beneficial effect. Remarkable hybrid vigour and the benefit effect of transgenes increased the fitness of hybrids together, but this joint effect was weakened by the compensation of wild plants. These results suggest that compensation to environmental stress may reduce the potential impacts of crop alleles on wild plants, thereby it is a mechanism maintaining the “wild” characteristics of wild populations under the scenario of continuous crop-wild gene flow.